Abilities of partial least-squares (PLS-2) multivariate calibration in the analysis of quaternary mixture of food Colors (E-110, E-122, E-124, E-131) - Karaoglan, G. Keser; Guemruekcue, G.; Ozgur, M. Ustun; Bozdogan, A.; Asci, B. (TAYLOR & FRANCIS INC, 2007)
Sunset Yellow (SY), Carmoisine (C), Ponceau 4R (P), and Patent Blue V (PB) are synthetic organic dyes which are under governmental regulations all over the world because of their toxicity and carcinogenicity. In this study, a simple and fast analytical procedure was proposed for the simultaneous determination of food dyes (SY, C, P, and PB) in powder drinks by means the partial least-square treatment of spectrophotometric absorbance between 450 730 nm, taken at 10 nm intervals. The experimental calibration matrix was constructed with 27 samples. The concentration ranges considered were 2, 3, 4 mu g. ml(-1) for SY, 7, 8, 9 mu g. ml(-1) for C, 9, 10, 11 mu g. ml(-1) for P, and 0.3, 0.4, 0.5 mg. ml(-1) for PB. The method was applied to the determination of dyes in different commercially available powder drinks. The results obtained by the application of the PLS-2 method were statistically compared with those obtained by an HPLC method using the F and t tests. Very similar values were found by two methods. No time consuming pretreatment was needed and this method also provides rapid, accurate and economical analysis of these colors.
Keywords: spectrophotometry; multivariate calibration; food colorants; sunset yellow; carmoisine; ponceau 4R; brillant blue; HPLC; SPECTROPHOTOMETRIC DETERMINATION; TERNARY MIXTURES; DERIVATIVE SPECTROPHOTOMETRY; SYNTHETIC COLORS; DYES; IDENTIFICATION; CHROMATOGRAPHY; CONFECTIONERY; Chemistry